Beograd '77 : Exposition Internationale des Arts Plastiques. - Muzej Savremene Umetnosti, Beograd; Protic, Miodrag B. (Beograd : Muzej Savremene umetnosti Beograd, 1977)
Angeli, Eduard ; Brus, Günter ; Gironcoli, Bruno ; Ortner, Hausrucker & Co. (Laurids ; Pinter, Klaus ; Kelp), Günter ; Jascha, Hans ; Jungwirth, Martha ; Pichler, Walter ; Rainer, Arnulf ; Schicho, Franz ; Sengl, Peter ; Alechinsky, Pierre ; Cox, Jan ; Moraes, Avatar ; Plaza, Julio ; Baev, Georgij ; Conev, Nikifor ; Docev, Petre ; Gorova, Maja ; Jaranov, Atanas ; Nedkova, Vera ; Petrova, Kristina ; Rusev, Svetline ; Sotirov, Stojan ; Stefanov, Kristo ; Stoicev, Emil ; Uzunov, Decko ; Fulla, Ludovit ; Gross, Frantisek ; Smetana, Jan ; Soucek, Karel ; Simerova, Ester ; Mortensen, Richard ; Huhtamo, Kari ; Kaivanto, Kimmo ; Petäjä, Matti ; Dewasne, Jean ; Hucleux, Jean-Olivier ; Raysse, Martial ; Diamantopoulos, Diamantis ; Droungas, Achilles ; Fassianos, Alekos ; Gaïtis, Yannis ; Georgiadis, Georgios ; Kanakakis, Lefteris ; Mytaras, Dimitris ; Takis ; Vakirtzis, Georgios ; Berghuis, Jaap ; Dibbets, Jan ; van Elk, Ger ; Pistoletto, Michelangelo ; Vago, Valentino ; Zaza, Michele ; Gvardijancic, Herman ; Mojovic, Dragan ; Sutej, Miroslav ; Velickovic, Vladimir ; Bolduc, David ; Gagnon, Charles ; Martin, Ron ; McEwen, Jean ; Molinari, Guido ; Rogers, Otto ; Bailey, Rhea ; Charalambides, Andreas ; Charalambous, Andreas ; Constantinoy, Demetris ; Diamantis, Adamantios ; Doriti, Maria ; Dymiotis, Nicolas ; Economou, Lefteris ; Kanthos, Telemachos ; Kouroussis, Nicos ; Ladommatos, Andreas ; Michaelidou, Stella ; Paraskos, Stass ; Savvides, Andreas ; Skotinos, Yorko ; Votsis, Stelios ; Frommelt, Martin ; Kliemand, Evi ; Malin, Georg ; Brandenburger-Brandy, Robert ; Claude, Gerard ; Kraus, Henri ; Leyder, Jean ; Asszonyi, Tamas ; Barcsay, Jeno ; Deim, Pal ; Feledi, Gyula ; Föth, Erno ; Gacs, György Z. ; Gross, Arnold ; Kerenyi, Jenö ; Kiss, Istvan ; Ko, Pal ; Kokas, Ignac ; etc.
biografie
Beograd '77 : Exposition Internationale des Arts Plastiques, Musée d'Art moderne de Belgrade; 1.10 - 1.12.1977
Frans
boek